The DALI vitamin D randomized controlled trial for gestational diabetes mellitus prevention: No major benefit shown besides vitamin D sufficiency. Issue 3 (March 2020) - Corcoy, Rosa; Mendoza, Lilian C.; Simmons, David; Desoye, Gernot; Adelantado, J.M.; Chico, Ana; Devlieger, Roland; van Assche, Andre; Galjaard, Sander; Timmerman, Dirk; Lapolla, Annunziata; Dalfra, Maria G.; et al.
Summary: Background & aims: As vitamin D deficiency is associated with an increased risk of gestational diabetes mellitus (GDM), we aimed to test vitamin D supplementation as a strategy to reduce GDM risk (evaluated after fasting plasma glucose (FPG), insulin resistance and weight gain) in pregnant overweight/obese women. Methods: The DALI vitamin D multicenter study enrolled women with prepregnancy body mass index (BMI) ≥ 29 kg/m 2, ≤19 + 6 weeks of gestation and without GDM. Participants were randomized to receive 1600 IU/day vitamin D3 or placebo (each with or without lifestyle intervention) on top of (multi)vitamins supplements. Women were assessed for vitamin D status (sufficiency defined as serum 25-hydroxyvitamin D (25(OH)D) ≥ 50 nmol/l), FPG, insulin resistance and weight at baseline, 24–28 and 35–37 weeks. Linear or logistic regression analyses were performed to assess intervention effects. Results: Average baseline serum 25(OH)D was ≥50 nmol/l across all study sites. In the vitamin D intervention arm ( n  = 79), 97% of participants achieved target serum vitamin 25(OH)D (≥50 nmol/l) at 24–28 weeks and 98% at 35–37 weeks vs 74% and 78% respectively in the placebo arm ( n  = 75, p  < 0.001). A small but significantly lower FPG (−0.14 mmol/l; CI95 −0.28,  −0.00) was observed at 35–37 weeks with the vitamin D intervention without any additional difference in metabolic status, perinatal outcomes or adverse event rates. Conclusion: In the DALI vitamin D trial, supplementation with 1600 IU vitamin D3/day achieved vitamin D sufficiency in virtually all pregnant women and a small effect in FPG at 35–37 weeks. The potential of vitamin D supplementation for GDM prevention in vitamin D sufficient populations appears to be limited. Trial registration number: ISRCTN70595832 Highlights: Vitamin D supplementation is an attractive candidate for GDM prevention. Baseline serum 25(OH)D was unexpectedly high and partly attributable to ethnicity. 1600 IU/day vitamin D supplementation achieved sufficiency at delivery in 96% women. A small reduction in FPG was observed in the vitamin D arm at 35–37 weeks. Vitamin D potential for GDM prevention is limited in women without deficiency.